Soil aggregates regulate the impact of soil bacterial and fungal communities on soil respiration - Yang, Chao; Liu, Nan; Zhang, Yingjun (Geoderma, 2019)
Soil aggregate size significantly impacts microbial communities and soil respiration. Soil total porosity and pH can regulate the distribution of soil bacteria and fungal communities within aggregates, thereby influencing soil respiration. However, it is unclear how it affects the microbial community composition distributed in soil aggregates, especially for fungal communities. The roles of soil total porosity and pH in controlling the microbial composition of soil aggregates are also unknown. In this study, we used high-throughput sequencing of the 16S rRNA and ITS gene regions to target bacterial and fungal members of aggregate samples of four sizes (2–4 mm, 1–2 mm, 0.25–1 mm and <0.25 mm). Our results showed that high respiration occurred in soil aggregates of 2–4 mm and 1–2 mm when there was high soil total porosity and low soil pH than in aggregates of 0.25–1 mm and <0.25 mm. Moreover, soil aggregates of 2–4 mm and 1–2 mm were dominated by four bacterial families (Oxalobacteraceae, Sphingomonadaceae, Cytophagaceae and Gemmatimonadaceae) and two fungal families (Lasiosphaeriaceae and Rhizophlyctidaceae), while the 0.25–1 mm and <0.25 mm aggregates were dominated by two bacterial families (Bacillaceae and Clostridiaceae) and one fungal family (Nectriaceae). Our results suggest that soil organic carbon and total porosity positively influenced the bacterial Shannon index, which led to a further positive influence on soil aggregate respiration, while soil pH positively affected the soil fungal Shannon index, leading to increased negative control of the respiration of soil aggregates. The structural equation modeling (SEM) results show that soil total porosity could directly influence soil respiration. In addition, soil organic carbon and total porosity had a significantly positive direct effect on bacterial Shannon index. Additionally, the soil pH showed a direct negative effect on fungal Shannon index and soil respiration. Soil bacterial and fungal Shannon index had a significantly positive and negative direct effect on soil respiration, respectively. Our study suggests that the difference distribution of soil organic carbon, pH, total porosity in aggregates controlling the soil microbial diversity, and then affect soil aggregate respiration. [Display omitted] •Soil aggregates size significantly impacts microbial communities and soil respiration.•High respiration occurred in macro-aggregates with high soil total porosity and low soil pH.•Soil bacterial Shannon index positively influenced the soil respiration.•Soil fungal Shannon index negatively affected the soil respiration.